Sternal wound management in pediatric cardiac surgical patients: implementation of wound care pathways incorporating principles of wound bed preparation paradigm and early-advanced therapy - Neerod Kumar, Muhammad Shafique, Raisy Thomas, Salvacion Pangilinan Cruz, Gulnaz Tariq, Laszlo Kiraly (WCET Journal - Chinese Edition, 2023)
Objective The information on sternal wound management in children after cardiac surgery is limited. The authors formulated a pediatric sternal wound care schematic incorporating concepts of interprofessional wound care and the wound bed preparation paradigm including negative-pressure wound therapy (NPWT) and surgical techniques to expedite and streamline wound care in children. Methods Authors assessed knowledge about sternal wound care among nurses, surgeons, intensivists, and physicians in a pediatric cardiac surgical unit regarding the latest concepts such as wound bed preparation, NERDS and STONEES criteria for wound infection, and early use of NPWT or surgery. Management pathways for superficial and deep sternal wounds and a wound progress chart were prepared and introduced in practice after education and training. Results The cardiac surgical unit team members demonstrated a lack of knowledge about the current concepts of wound care, although this improved after education. The newly proposed management pathway/algorithm for superficial and deep sternal wounds and a wound progress assessment chart was introduced into practice. Results in 16 observed patients were encouraging, leading to complete healing and no mortality. Conclusions Managing pediatric sternal wounds after cardiac surgery can be streamlined through incorporation of evidence-based current wound care concepts. In addition, the early introduction of advanced care techniques with appropriate surgical closure further improves outcomes. A management pathway for pediatric sternal wounds is beneficial.